Penentuan Subsektor Unggulan Pembangunan Ekonomi Inklusif dan Berkelanjutan Menggunakan Metode Promethee: Studi Kasus Calon Daerah Otonom Baru Kabupaten Sukabumi Utara - Ernan Rustiadi; Abdul Naafi AR; Bambang Juanda; Hania Rahma (Research and Development Agency Ministry of Home Affairs, 2025)
Inclusive and sustainable economic development is a very important and relevant approach to be applied in various regions in Indonesia, including in areas that are in the process of becoming new autonomous regions, namely North Sukabumi Regency. This approach aims to create economic growth that not only encourages increased income but also ensures that the benefits are felt by all levels of society, including marginalized groups, while maintaining ecosystem balance and creating a better future generation. This study analyzes potential economic leading sectors to promote inclusive and sustainable economic development. The selection of leading sectors was carried out using the Promethee method, which is an outranking-based multi-criteria analysis (MCA) method based on a preference index. A total of 12 criteria were used, and data were obtained through questionnaires from several experts. The results of this study indicate that the development of the Food Crops, Horticulture, and Food and Beverage Industries subsectors is a potential sector recommended for promoting inclusive and sustainable economic development.